Viral Regulation of Prokaryotic Carbon Metabolism in a Hypereutrophic Freshwater Reservoir Ecosystem (Villerest, France) - Pradeep Ram, Angia Sriram; Colombet, Jonathan; Perriere, Fanny; Thouvenot, Antoine; Sime-Ngando, Télesphore (Frontiers in Microbiology, 2016)
The current consensus concerning the viral regulation of prokaryotic carbon metabolism is less well studied, compared to substrate availability. We explored the seasonal and vertical distribution of viruses and its relative influence on prokaryotic carbon metabolism in a hypereutrophic reservoir, Lake Villerest (France). Flow cytometry and transmission electron microscopy analyses to determine viral abundance (range = 6.1 - 63.5 x 107 ml-1) and viral infection rates of prokaryotes (range = 5.3 - 32%) respectively suggested that both the parameters varied more significantly with depths than with seasons. Prokaryotic growth efficiency (PGE, considered as a proxy of prokaryotic carbon metabolism) calculated from prokaryotic production and respiration measurements (PGE = prokaryotic production/[prokaryotic production + prokaryotic respiration] x 100) varied from 14 to 80% across seasons and depths. Viruses through selective lyses had antagonistic impacts on PGE by regulating key prokaryotic metabolic processes (i.e. production and respiration). Higher viral lysis accompanied by higher respiration rates and lower PGE in the summer (mean = 22.9 ± 10.3%) than other seasons (mean = 59.1 ± 18.6%), led to significant loss of carbon through bacterial-viral loop and shifted the reservoir system to net heterotrophy. Our data therefore suggests that the putative adverse impact of viruses on the growth efficiency of the prokaryotic community can have strong implications on nutrient flux patterns and on the overall ecosystem metabolism in anthropogenic dominated aquatic systems such as Lake Villerest.